Teori Dewan Pengawas Syariah - Setiawan, Rahmat (JSE: Jurnal Sharia Economica, 2025)
The purpose of this study is to find the theory of the Sharia Supervisory Board to improve the role of the Sharia Supervisory Board. This study uses a descriptive qualitative approach. The discussion of the theory of the Sharia Supervisory Board is explained in detail and structured to provide an in-depth explanation of the Sharia Supervisory Board theoretically. The results of the study found that the theory of the Sharia Supervisory Board (SSB) shows that the SSB theory is shaped like a building where the foundation of the SSB is the faith based on the Al-Quran and Al Hadith and carries out the nature of the Prophet Muhammad SAW. Once the foundation is in place, it can carry out its duties and responsibilities as a SSB based on sharia which consists of supervising sharia compliance, recommendations for the development of new products and services, strategic management advisors and making reports and opinions on the results of supervision. If the duties of the SSB have been carried out correctly in sharia banking, sustainable sharia banking activities will be realized in accordance with sharia so that they receive the blessing of Allah Ta'ala. The benefits of this Sharia Supervisory Board theory are to increase knowledge and science in the academic world in providing rules and guidelines that must be carried out by the DPS in carrying out its duties to supervise the activities of Islamic banks to ensure that Islamic bank activities are in accordance with the fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI).